Comparative study for antibiotic susceptibility against ?Pseudomonas aeruginosa isolated from otitis media through ?several years in Thi-Qar Province/Iraq - Saad Abdul Azeez Atiyah (University of Thi-Qar Journal, 2022)
Otitis media is a common worldwide health care problem infects peoples at different ages, Pseudomonas aeruginosa is the most frequent causative agent responsible for the disease with high ability to resists antibiotics. The study aimed to compare the developments of antibiotic resistance among Pseudomonas. aeruginosa through some years. The study including (77) specimens were positive for P. aeruginosa collected in Al-Habobi teaching hospital in Al-Nasiriyah city/South of Iraq through the periods from 2015 to 2020, antibiotic susceptibility test was done by disc diffusion technique. The results revealed no significances in the infections between two genders, But the isolates showed high significant differences ( p value ? 0.001) according to years and the Amikacin is the most effective antibiotic against this bacteria (64.9%). In brief, The study showed no differences in antibiotic susceptibility of P. aeruginosa in the years of study with high resistance for several antibiotics and the Amikacin was most effective antibiotic against P. aeruginosa isolates causing otitis media